1988
DOI: 10.1111/j.1530-0277.1988.tb00235.x
|View full text |Cite
|
Sign up to set email alerts
|

4‐Methylpyrazole: A Controlled Study of Safety in Healthy Human Subjects after Single, Ascending Doses

Abstract: 4-Methylpyrazole (4-MP), an inhibitor of alcohol dehydrogenase, is a possible future drug for the treatment of methanol and ethylene glycol intoxications and the severe ethanol-disulfiram reaction. Therefore a placebo-controlled, double-blind, single-dose, randomized, sequential, ascending-dose "Phase I study" was performed in healthy volunteers in order to determine the tolerance of 4-MP at dose levels of 10 (n = 4), 20 (n = 4), 50 (n = 4), and 100 mg/kg (n = 3). Along with each dose group, there were two pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
34
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 33 publications
2
34
0
Order By: Relevance
“…Side-effects of classical ethanol therapy such as hypoglycaemia and [17]. Commonly reported adverse events in clinical trials are headache, nausea and dizziness [12]. Less frequent sideeffects are phlebitis, dyspepsia, agitation, anxiety, hiccup, rash, transient tachycardia, seizures, headache and bradycardia [5,6].…”
Section: Discussionmentioning
confidence: 98%
“…Side-effects of classical ethanol therapy such as hypoglycaemia and [17]. Commonly reported adverse events in clinical trials are headache, nausea and dizziness [12]. Less frequent sideeffects are phlebitis, dyspepsia, agitation, anxiety, hiccup, rash, transient tachycardia, seizures, headache and bradycardia [5,6].…”
Section: Discussionmentioning
confidence: 98%
“…Fomepizole was well tolerated, in spite of prolonged administration (up to 8 days) in three patients. Jacobsen and colleagues [30] have shown that fomepizole is well tolerated in healthy human subjects in therapeutic doses, with no significant changes in clinical or laboratory, including liver function tests.…”
Section: Discussionmentioning
confidence: 99%
“…administered fomepizole to healthy human volunteers in single oral doses ranging from 10 to 100 mg/kg. At doses of 50 and 100 mg/kg, subjects experienced nausea and vertigo but there were no alterations in pulse or blood pressure (9). The methylpyrazole for toxic alcohols (META) study group conducted carefully monitored, unblinded clinical trials evaluating intravenous fomepizole (10-15 mg/kg/ dose) in 19 patients with ethylene glycol poisoning and 11 patients with methanol poisoning (10-11).…”
Section: Discussionmentioning
confidence: 99%